Penggunaan KOH String Test Sebagai Alternatif Identifikasi Awal Bakteri Gram Negatif - Elisa Rinihapsari; Shelfi Julianasya (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
KOH string test is a simple identification method without staining, requiring only one reagent to determine the Gram reaction in bacteria. Considering the simplicity of this method, its use needs to be introduced further. However, to ensure the validity of this method, research needs to be carried out to verify the results of the KOH string test when compared with the identification method using Gram staining, which is the gold standard. This study aimed to determine whether there is a difference in the identification results between Gram staining and the KOH string test in determining the Gram characteristics of bacteria, especially Gram-negative bacteria, to find out whether there is a difference in the length of mucus produced from the KOH string-test between KOH reagent concentrations of 1, 3, and 5%, as well as knowing the KOH concentration that was best used for bacterial identification with the KOH string test. The results of the study showed that there was no difference in results between identification using Gram staining and the KOH string test. Statistical results showed a significant difference between the mucus lengths of the three reagent concentrations, and 3% KOH was the recommended reagent for use in the KOH string test method.